Students’ considerations on the resistance actions during the Chilean dictatorship from the ethical dimension of historical thinking - Soto Yonhson, Andrés (2024)
The purpose of this article is to analyze the motivations and relevance attributed by students to the individual and collective resistance actions developed by citizens during the Chilean dictatorship. This is exploratory qualitative research that analyzes 70 responses developed by 35 high school students in a private school in Santiago, Chile. The results show that the participants believe that the historical subjects organized themselves against the dictatorship for general and ahistorical motivations (defense of human rights, loss of fear and desire for change), and they also value and point out that collective citizen actions were the main cause of the fall of the dictatorship commanded by Pinochet. The latter demonstrates the need to complexify and work explicitly and systematically the difficult histories from the ethical dimension of historical thought.